Permasalahan Perkembangan Peserta Didik Di Sekolah Dasar Akibat Bullying - Eka Bagus Pramudya; Diah Puri Widyawati; Tasya Putri; Dinda Zahra Ummami; Panji Adi Nugroho (CV. ITTC INDONESIA, 2024)
Bullying in elementary schools is a significant issue that can affect the physical, emotional, and social development of students. This research aims to identify the impact of bullying on the development of elementary school students, focusing on psychological, academic, and social relationship aspects. The study finds that students who experience bullying tend to exhibit decreased learning motivation, poor academic performance, and emotional disturbances such as anxiety and depression. Moreover, bullying victims often face difficulties in building healthy peer relationships. Therefore, efforts from schools, teachers, and parents are needed to create a safe and supportive environment to reduce and prevent bullying cases, as well as to facilitate the optimal development of students